PERAN PEMERINTAH KABUPATEN KAMPAR DALAM PENGEMBANGAN PERPUSTAKAAN DESA TAHUN 2018-2020 - Muhammad Muhyidin; Wan Asrida (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
Each district only has a few villages that have a village library, and it is rare for a village that has a village library to have complete facilities as well as adequate books and services, and most libraries in the village are only for building displays. Riau Province. In the Regent's Regulation Number 55 of 2016 concerning the Job Description of the Kampar Regency Library and Archives Service in article 6, "The field of library development has the task of organizing the formulation of technical policy materials for library development", in this article it is explained that the Kampar Regency Library and Archives Service has duties in the field of development of libraries, especially the development of village libraries. The lack of role of the Kampar Regency Government in the development of village libraries has caused one of the libraries in Kampar Regency, namely the Rimbo Panjang village library, to not be able to implement the national guideline standard for village libraries.The purpose of this study is to describe the role of the Kampar Regency Government in the development of the village library in 2018-2020 and to describe the inhibiting factors of the Kampar Regency Government's role in the development of the village library in 2018-2020. This study uses a qualitative approach with a descriptive method. In collecting data, the author uses interview and documentation techniques.The results of this study found that the role of the Kampar Regency Government as a facilitator in the development of the village library was not maximized, especially the uneven distribution of education and training activities, assistance or funding, the role of the Kampar Regency Government as a regulator in the development of village libraries and the role of the Kampar Regency Government as a regulator has not been maximized. motivator in the development of village libraries, especially the lack of socialization and encouraging the community to participate. Keywords: Role, Village Library Development